Sequencing, Cloning And Expression Of The Newcastle Disease Virus Fusion Protein Gene Of Strain Af2240 - Mohammed, Omeima Salih (1999)

(untitled)
Newcastle disease is a highly contagious viral disease of poultry and has greater than 95 % morbidity and mortality. The etiological agent, Newcastle disease virus (NOV) , is a member of the family Paramyxoviridae and the genus Rubulavirus. Immune responses to the fusion protein (F) antigen of NOV were demonstrated to play an important role in the prevention of infection. Accordingly, the F gene of a Malaysian heat-resistant NOV velogenic-viscerotropic strain A F2240 was amplified and cloned into pCR™2 . 1 vector. Its sequence was determined by sequencing of the cloned F gene RT-PCR products. It contains 1791 nucleotides and encodes a large ORF of 553 amino acids. The deduced amino acid sequences of the Fo precursor protein has a pair of dibasic residues with an intervening glutamine (Q) at the proteolytic site, three hydrophobic regions and six asparginine glycosylation sites. The cleavage-activation site as well as part of the fusion-inducing sequence were compared among a series of virulent and avirulent NOV strains using multiple